Динамика нарастания ботвы и корнеплодов свеклы столовой при использовании биостимуляторов - Руслан МЯЛКОВСКИЙ (Stiinta Agricola, 2021)
The article presents the results of studies of the influence of biostimulants on the dynamics of growth of the leaf area of red beet plants and the mass of beet roots in the Western Forest-Steppe of Ukraine. It was determined that the best way to apply biostimulants was the method of seed treatment in both studied variet-ies compared to foliar application during the growing season. In the variants where pre-sowing treatment of seeds with growth regulators was used, the area of leaves for the period of row closure was 2202.31-2770.65 cm2/plant (Akela) and 1221.28-1497.33 cm2 plant (Bicores). It should be noted that plants of both varieties had the largest leaf area after application of the growth regulator Regoplant compared with the growth regulators Endophyte L1 and Vympel K. Pre-sowing seed treatment with the growth regulator Regoplant provided the highest weight of beet roots: 357.33 g (Akela) and 331.45 g (Bicores), which is 128.33 g and 100.12 g higher than the control. Therefore, according to research, the most effective growth regulator was Regoplant, which was used for seed treatment.